(untitled) (Research, Society and Development, 2023)
The objective of this study was to identify the main behavioral and emotional reactions manifested in surgical patients in the preoperative phase, since the subjective experience of the patient in this phase can have repercussions on the others. The present work is configured as an integrative literature review, with a search or sampling of literature in databases of electronic journals, using selected keywords in DECS (Descriptors in Health Sciences) and inclusion and exclusion criteria to select the most relevant articles on the subject. As a result, nine articles were included in this study, seven of the experimental type and two of the observational type, which brought as evidence two emotional and behavioral reactions more recurrent in the pre-surgical period: reactive anxiety and psychological-organic stress. In addition, the articles showed how the practices of psychoeducation and use of materials managed to reduce levels/scores of both physical (blood pressure, high cortisol) and psychological (anxiety, stress, fear) during the preoperative period. It was concluded that pronounced anxiety and stress can significantly interfere both in the preoperative stage and in postoperative recovery, being significant the intervention of the multidisciplinary team in the management and support to the surgical patient, being able to use resources ranging from preoperative communication and therapeutic listening as the use of materials to reduce and alleviate the deleterious effects of this stage.